Impact of Solute Properties and Water Matrix on Nanofiltration of Pesticides. Issue 9 (11th June 2019) - Tan, Lian See; Ahmad, Abdul Latif; Shukor, Syamsul Rizal Abd; Yeap, Swee Pin
Abstract: The application of different nanofiltration membranes for the separation of pesticides, i.e., atrazine and dimethoate, from aqueous solutions is described. The nanoflitration membranes DK, NF270, NF200, and NF90 were tested for the pesticide retention performance in a stirred dead‐end filtration system. NF90 demonstrated the best pesticide retention with over 95 % for atrazine and approximately 80 % for dimethoate. All membranes consistently showed better retention of atrazine than of dimethoate. Dissolving the pesticides in river or tap water amplified the overall pesticide retention performance, indicating that filtration in water treatment plants could render superior pesticide retention. However, a lower flux was obtained for the filtration of tap and river water. Abstract : Different nanofiltration membranes are evaluated for the separation of the pesticides atrazine and dimethoate from different water matrix solutions. Dissolving the pesticides in river or tap water amplified the overall pesticide retention performance. However, for this case a lower flux is obtained as compared to the case when the pesticides are dissolved in either distilled or deionized water.